Enhancing Nurses’ Knowledge and Documentation Skills Through 3S Training (SDKI, SLKI, SIKI): A Quasi-Experimental Study - Rachmawaty, Lusy; Wisuda, Aris Citra; Sujariah, Fitri; Wijaksana, M. Agung; Sidik, Abu Bakar; Agustina, Novita; Suraya, Citra (Yayasan Rumah Ilmu Professor, 2025)
The quality of nursing documentation in Indonesia remains low, with an achievement rate of only 7%, far below international standards. The Indonesian National Nurses Association (Persatuan Perawat Nasional Indonesia/PPNI) has developed the Triple S (SDKI, SLKI, SIKI) documentation standards to improve the quality of nursing documentation. To analyze the effect of 3S training on nurses’ knowledge and skills in nursing care documentation at RSUD Gelumbang. A quasi-experimental study with a nonequivalent control group pretest-posttest design was conducted, involving 50 nurses who were divided into an intervention group (n=25) and a control group (n=25). The intervention group received 3S training over a period of two days, while the control group received no intervention. Data were analyzed using Independent T-Test, Paired T-Test, Mann-Whitney, and Wilcoxon tests. The 3S training had a significant effect on nurses’ knowledge (p = 0.000 < 0.05), with an average score increase from 48.60 to 74.40. However, it did not have a significant effect on skills (p = 0.585 > 0.05). The 3S training was effective in improving nurses’ knowledge, but a comprehensive approach is required to enhance practical skills.